Influence of infill depth and fibre height of artificial turf on rotational traction - Ruschkowski, J.; Varughese, J. M.; Stefanyshyn, D. J.; Wannop, J. W. (Sports Engineering, 2024)
Artificial turf is a widespread surface used for various field sports, offering unique advantages to natural grass such as all-weather availability and durability. This study aimed to determine the influence of infill depth and the exposed fibre height on shoe-surface traction for artificial turf surfaces. Particular focus was placed upon rotational traction, which has been associated with lower extremity injuries in sports. Ten artificial turf surfaces with varying infill depth and exposed fibre length were mechanically tested, with results indicating a significant impact of infill depth on rotational traction (F = 3.150, p = 0.017, = 0.104); as infill depth increased, a reduction in rotational traction was observed. For surfaces with longer carpet fibres, a trend to a significant correlation between exposed carpet fibre length and rotational traction was also observed (R2 = 0.7236, p = 0.068). Exposed fibre lengths above 18-20 mm were associated with an increase in rotational traction. Results suggest that at around 12-18 mm, any further reduction in exposed fibre length may have little to no influence on rotational traction. These findings have implications for player safety, aligning with prior research linking excessive rotational traction to elevated injury risks and highlight the importance of maintaining prescribed infill depths and exposed fibre lengths on artificial turf surfaces.